Asthma and Atopic Diseases in Children with Autism Spectrum Disorders - Khaled Saad; Mohamed Ezzat; Amira Elhoufey; Mahmoud Elsaeed Ahmed; Abdulrahman A. Al-Atram; Mohsen M. Fageeh; Yasser Hamed (Journal of Pharmacy and Bioallied Sciences)
Objective: Autism spectrum disorders (ASD) and atopic diseases are prevalent conditions affecting numerous children globally, with rising incidence rates. While both environmental and genetic factors are involved, the precise cause of this rise remains elusive. This study aims to assess the frequencies of atopic diseases in a cohort of Egyptian children with ASD. Patients and Methods: We employed a survey consisting of 23 points relating to atopic conditions, which were modified from the International Study of Asthma and Allergies in Childhood (ISAAC). Parents of all participants with ASD and controls completed the questionnaires. Results: Our study included 150 ASD and 100 control children. All allergic diseases were significantly higher in ASD patients except food allergy. Conclusion: Allergic diseases are complex conditions influenced by both genetic predisposition and environmental factors, which play pivotal roles in their development. Our investigation has revealed a heightened prevalence of allergic diseases alongside ASD, reinforcing the link between ASD and allergic conditions. Hence, further comprehensive studies with larger sample sizes are warranted to thoroughly assess and validate these findings.